Inter-trial priming does not affect attentional priority in asymmetric visual search - Amunts, Liana; Yashar, Amit; Lamy, Dominique (Frontiers in Psychology, 2014)
Visual search is considerably speeded when the target’s characteristics remain constant across successive selections. Here, we investigated whether such inter-trial priming increases the target’s attentional priority, by examining whether target repetition reduces search efficiency during serial search. As the study of inter-trial priming requires the target and distractors to exchange roles unpredictably, it has mostly been confined to singleton searches, which typically yield efficient search. We therefore resorted to two singleton searches known to yield relatively inefficient performance, that is, searches in which the target does not pop out. Participants searched for a veridical angry face among neutral ones or vice-versa, either upright or inverted (Experiment 1) or for a Q among Os or vice-versa (Experiment 2). In both experiments, we found substantial intertrial priming that did not improve search efficiency. In addition, intertrial priming was asymmetric and occurred only when the more salient target repeated. We conclude that intertrial priming does not modulate attentional priority allocation and that it occurs in asymmetric search only when the target is characterized by an additional feature that is consciously perceived.